THE SOIL CARBON STOCK IN THE TOURISM AREA OF GILI TRAWANGAN - Astuti, Eni Widia; Bakti, Lalu Arifin Aria; Kusnarta, IGM; Selvia, Siska Ita (AGROTEKSOS; Vol 33 No 2 (2023): Jurnal Agroteksos Agustus 2023, 2023)
This study aims to determine the distribution of carbon stocks in various land uses and total carbon stocks in the tourism area of ​​Gili Trawangan. This research was conducted in the Gili Trawangan area, Physics and Soil Conservation Laboratory, and Soil Chemistry and Biology Laboratory, Faculty of Agriculture, University of Mataram, in June-October 2022. The method used in this study was a descriptive method with a survey technique. The descriptive method can start with data collection, analysis and interpretation. Carbon in the soil in this study was obtained from the results of C-organic laboratory analysis (Walcky and Black) supported by measurements of soil unit weight (BV), soil porosity and soil texture. Meanwhile, aboveground carbon stocks were obtained through direct sampling in the field by measuring tree biomass. The results showed that the total carbon stocks in various land uses have different carbon stocks. The mixed garden had the highest carbon stock of 840.27 ton.ha-1, forest land of 83.76 ton.ha-1, and shrubs of 15.76 ton.ha-1, and the lowest carbon stock was a settlement of 3.01 ton. ha-1. Overall, carbon stocks in the tourist area of ​​Gili Trawangan are 942.8 ton.ha-1.